Economic, technological, and institutional factors affecting international tourism in MENA countries - Abid, Ihsen (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to identify and analyze the key determinants of international tourism in the MENA region, offering empirical insights into how economic, sectoral, and digital factors affect tourism demand. The research utilizes panel data from MENA countries spanning 1990 to 2023 and applies a fixed-effects regression model with Driscoll-Kraay standard errors to address issues of cross-sectional dependence and heteroskedasticity. The independent variables include foreign direct investment (FDI), exchange rates, inflation, internet penetration, agricultural and manufacturing value added, and regulatory quality. The empirical results indicate that FDI, exchange rates, and internet penetration have a statistically significant and positive impact on international tourism arrivals. Conversely, agricultural sector dependence negatively influences tourism inflows. No significant effects were found for inflation, manufacturing, or regulatory quality. Economic openness through FDI, a favorable exchange rate, and greater internet accessibility are crucial to enhancing international tourism in MENA countries. However, a heavy reliance on agriculture may hinder tourism development. The study provides actionable insights for policymakers aiming to strengthen the tourism sector and promote broader economic diversification. Enhancing digital infrastructure, attracting FDI, and shifting away from agricultural dependence can help boost tourism competitiveness in the region. This study enriches the literature by focusing on the underexplored MENA context and integrating economic, digital, and structural determinants of tourism demand.